The Meaning and Experience of Muslim UMKM Actors on the Application of Sharia Economic Principles in Micro-Business Management A Phenomenological Study in Indonesia - Deden Hidayat; Osmiati Osmiati (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
This study explores the meaning and lived experiences of Muslim micro, small, and medium enterprise (UMKM) actors in applying Sharia economic principles within micro-business management in Indonesia. Using a phenomenological approach, this research seeks to understand how Islamic values such as honesty (ṣidq), trustworthiness (amānah), justice (‘adl), and the prohibition of riba are interpreted and practiced in daily business activities. Data were collected through in-depth interviews, observations, and documentation involving selected Muslim UMKM actors who actively integrate Sharia principles into their businesses. The findings reveal that the application of Sharia economic principles is not merely normative but becomes a moral and spiritual foundation guiding business decisions, financial management, and customer relations. Participants perceive their businesses not only as profit-oriented entities but also as a form of worship (‘ibādah) and social responsibility. However, challenges remain, including limited literacy on Islamic finance, market competition, and inconsistencies in implementation. Despite these obstacles, the commitment to ethical business practices rooted in Islamic teachings strengthens trust, sustainability, and business resilience. This study contributes to the development of Islamic economic discourse by highlighting the experiential dimensions of Sharia implementation at the micro level, offering insights for policymakers, educators, and practitioners in promoting inclusive and value-based economic practices in Indonesia.